Stuck on stubble? The non-market value of agricultural byproducts for diversified farmers in Morocco - Magnan, Nicholas; Larson, Douglas M.; Taylor, J. Edward (Wiley, 2012)
Diversified agricultural households often use byproducts of one activity as inputs for another. For crop‐livestock farmers, cereal production provides grain and crop residue, where the latter can be used as livestock feed. To properly assess the cost of introducing new technologies into such systems, one must value the implicit cost of byproducts, which is made difficult by missing byproduct markets. We estimate the shadow value of non‐market crop stubble using household data from Morocco and find that stubble accounts for around one‐quarter of the value of cereal production in a normal rainfall year and three quarters in a drought year.